Zasoby opiekunów osób starszych i ich uwarunkowania - Brzezińska, Anna Izabela; Wójcik, Sylwia (Wydawnictwo Naukowe UAM, 2012)
The research aim is identifying factors which may have an effect on the attitude of carers of the elderly towards their work. The goal is also to specify the areas where support could be offered to enable caregivers to experience the feelings of pleasure, involvement and sense in relation to their work. The study encompassed 98 participants, workers of four care homes for the elderly located in the Wielkopolska region. The study was conducted by means of two questionnaires: The assessment of the size of possessed resources and The perceived importance of possessed resources. The resources investigated were divided into two categories: subjective (internal) and environmental (external). The importance of the resources proved to be more significant for caregivers than their size. Furthermore, the respondents assessed current resources as smaller and less important as a source of support for them in difficult situations than the resources coming from earlier periods of life. As a result of the performed cluster analysis (k-means method) five subgroups of carers were identified according to the similarity of the assessment of both the size and importance of their resources; the subgroups were labelled: “Uncritical faith in the environment”, “Critical of the role of the environment”, “Malcontents”, “Critical of oneself”, “Convinced about one’s worth”.
Resources of caregivers of elderly people and their determinants
Keywords: external resources; internal resources; pleasure; involvement; sense